TAFSIR BI AL-RAâYI SEBAGAI SALAH SATU BENTUK PENAFSIRAN ALQURAN (Hunafa: Jurnal Studia Islamika, 2005)
Tafsir bi al-Raâyi is one of methods employed by ulama in interpreting the Holy Qurâan. The reason for interpreting the Holy Qurâan usingÂ  reasoning is that there are many ayahs (verses of the Qurâan) encourageÂ  us toÂ  think . However, some of ulama Â prohibitÂ  the use of reason in interpreting the Qurâan because some ofÂ  their interpretations are not compatible with the true massage of the Holy Qurâan. Consequently, their interpretation aims at supporting their own interest only.Key word:Â  Tafsir bi al-Raâyi,Â  bentuk penafsiran,Â  Alquran